Perspective Directions of Multilateral Cooperation between the EU and the PRC in the Context of Stabilizing the Global Financial System - BIRIMKULOVA, Gulnara U.; ZHYLKYBEKULY, Bekkozha; TASHTEMKHANOVA, Raihan (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018, 2019)
The relevance of the study is determined by the fact that the European Union and China are two powerful trading partners with the largest economies in the world. China is now the second EU trade partner after the United States. The authors show that the EU intends to further extend trade and economic relations with China, but at the same time strives for more reliable guarantees of trade with China to comply with fair and transparent trade rules, and to fulfill bilateral obligations under the WTO. The novelty of the study is determined by the fact that negotiations on a well-rounded investment agreement between the European Union and China were analyzed in the framework of EU-China cooperation. The authors determine the need for a gradual liberalization of investment and the elimination of restrictions for investors in each other’s markets. This will provide a simpler and safer legal basis for investors from both sides, providing them with reliable protection and their investments. The authors found out that China planned reforms in the economic and financial sectors to strengthen trade and economic cooperation with the EU.